Development of Competency-Based Assessment Instruments in PAI Subjects - Rosmiati Ramli; Sudirman Herman; Nurhidaya Da’te; Wisriani; Nafsia Marasabessy (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The development of competency-based assessment instruments in Islamic Religious Education (Pendidikan Agama Islam/PAI) is an essential effort to improve the quality of comprehensive and meaningful learning evaluation. Competency-based assessment emphasizes not only cognitive aspects but also affective and psychomotor domains, which are fundamental characteristics of PAI learning. This study aims to describe the concept, process, and implementation of developing competency-based assessment instruments in the PAI subject. The method used is a qualitative descriptive approach through the analysis of curriculum documents, relevant literature, and assessment practices in schools. The findings indicate that competency-based assessment instruments in PAI should be designed based on core competencies and basic competencies, supported by clear and measurable indicators, and implemented using various authentic assessment techniques such as observation of religious attitudes, assessment of worship practices, project-based assignments, portfolios, and written tests. Systematically and integratively developed instruments are able to provide a more comprehensive picture of students' competency achievement, particularly in terms of knowledge, religious attitudes, and skills in practicing Islamic values. Therefore, competency-based assessment instruments are expected to support the achievement of PAI learning objectives optimally and sustainably.